2005
DOI: 10.1152/jn.01114.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pitch of Complex Tones: Rate-Place and Interspike Interval Representations in the Auditory Nerve

Abstract: Harmonic complex tones elicit a pitch sensation at their fundamental frequency (F0), even when their spectrum contains no energy at F0, a phenomenon known as "pitch of the missing fundamental." The strength of this pitch percept depends upon the degree to which individual harmonics are spaced sufficiently apart to be "resolved" by the mechanical frequency analysis in the cochlea. We investigated the resolvability of harmonics of missing-fundamental complex tones in the auditory nerve (AN) of anesthetized cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
114
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(132 citation statements)
references
References 82 publications
(114 reference statements)
17
114
1
Order By: Relevance
“…Thus, the limits of tonotopic resolution illustrated in the model likely reflect peripheral limitations that are maintained throughout the tonotopic areas of the auditory pathways. This conclusion is supported by a recent study in the cat auditory nerve, which showed that the highest resolved harmonic varied from around the fifth at an f 0 of 200 Hz to around the 10th at an f 0 of 1000 Hz (Cedolin and Delgutte, 2005). Thus, even if human tuning is sharper than that found in cat by a factor of 2 (Shera et al, 2002), within our range of f 0 s (Ͻ 200 Hz) we would not expect harmonics above the 10th to be resolved in the auditory periphery or beyond.…”
Section: Methodssupporting
confidence: 74%
“…Thus, the limits of tonotopic resolution illustrated in the model likely reflect peripheral limitations that are maintained throughout the tonotopic areas of the auditory pathways. This conclusion is supported by a recent study in the cat auditory nerve, which showed that the highest resolved harmonic varied from around the fifth at an f 0 of 200 Hz to around the 10th at an f 0 of 1000 Hz (Cedolin and Delgutte, 2005). Thus, even if human tuning is sharper than that found in cat by a factor of 2 (Shera et al, 2002), within our range of f 0 s (Ͻ 200 Hz) we would not expect harmonics above the 10th to be resolved in the auditory periphery or beyond.…”
Section: Methodssupporting
confidence: 74%
“…Surprisingly, neural resolvability of double HCT harmonics in A1 is comparable with or greater than that observed in the auditory nerve of the anesthetized cat, where responses to HCTs tend to saturate at moderate to high stimulus levels (Cedolin and Delgutte, 2010). Despite their relatively high level in the present study (60 dB SPL per component), many of the lower harmonics of the double HCTs were well resolved in rate-place profiles.…”
Section: Discussionmentioning
confidence: 73%
“…Using a stimulus design employed in auditory nerve studies of pitch encoding (Cedolin and Delgutte, 2005;Larsen et al, 2008), the present study examined whether spectral and temporal information sufficient for extracting the F0s of two simultaneously presented HCTs, a prerequisite for their perceptual segregation, is available at the level of A1. F0s of the concurrent HCTs differed by 4 semitones, an amount sufficient for them to be reliably heard as two separate auditory objects with distinct pitches in human listeners (Assmann and Paschall, 1998;Micheyl and Oxenham, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, neither the sigmoidal shape of rate-level functions (firing rate as a function of stimulus SPL), their dynamic range, nor maximum firing rate, are dependent on stimulus frequency per se but on stimulus frequency relative to characteristic frequency (CF). This behavior, combined with cochlear band-pass filtering, underlies rate-place coding: spectral components are translated into a firing rate profile of the population of AN fibers (Cedolin and Delgutte 2005;). This is a tonotopic or "vertical" view of the audi-tory system in which strength of response along the tonotopic axis is proportional to spectral energy.…”
Section: An To Brain Stem: a Change In Orientationmentioning
confidence: 99%